Algoritma sebagai Mimbar: Analisis Personalisasi Konten Keagamaan pada Media Sosial terhadap Moderasi Beragama - Azi Gunawan (IKHBAR: Jurnal Ilmu Dakwah dan Komunikasi, 2026)
In the digital era, religious authority has undergone a significant shift from physical pulpits in mosques to "algorithmic pulpits" on social media. This study aims to analyze how content personalization mechanisms and filter bubbles affect perceptions of religious moderation among users. Social media algorithms are designed to maximize engagement by presenting content tailored to user preferences, inadvertently creating echo chambers. Using a qualitative method with a literature review and critical discourse analysis approach, this research explores the psychological and sociological impacts of this automated content curation. The results indicate that algorithms tend to reinforce confirmation bias, where users are exposed only to religious narratives that validate their pre-existing views, while isolating them from divergent perspectives (the religious other). This potential erodes the values of religious moderation (wasathiyah), which emphasizes balance and tolerance, and fosters polarization and extremism based on decontextualized texts. The study concludes that algorithmic literacy is essential as part of religious literacy, preventing believers from being trapped in blind fanaticism constructed by machines.